Jummy at the River School - Adeyinka, Sabine (Nigeria, 2022)
Jummy has earned a place at the River School, the finest girls' boarding school in Nigeria. Nothing can dampen her spirits, not even when she learns that her less fortunate best friend Caro won't be joining her. By the Shine-Shine River, school is everything Jummy dreamt of, with friendly new girls, midnight feasts and sporting prizes. But when Caro suddenly arrives at the school to work, not to learn, Jummy must bring all her friends together to help...
Keywords: Adventure; Juvenile Fiction